Identifying false hadith guidelines - Rohaizan, Baru; Basri, Ibrahim; Syed Hadzrullathfi, Syed Omar (2017)
A false hadith is hadith that has been created, fabricated or falsified in the name of Prophet SAW, either intentionally or otherwise. The dissemination of falsified hadith has a negative impact on the aqidah and syariah. It could raise questions on the authenticity of the hadith and also raise doubts when accepting the hadith as a source of legal reference. The religious scholar who contributed most in safeguarding the sanctity of the hadith was Imam Ibn Qayyim al-Jauziyyah (IQJ) with his scripture entitled Naqd al-Manqul. This article focused on several general views adduced by IQJ on identifying falsified hadith so that people would be able to identify it, beware of disseminating falsified hadith, and subsequently contribute towards eradicating the spread of falsified hadith in society. Religious scholars and academicians should play a role in disseminating authenticated hadith and provide explanations and information on falsified hadith if it exists.